Indonesia's Sea Defense Strategy in the IKN Nusantara: Smart Defense and Dual Strategy - Hafidz Kuncoro Jati; Lukman Yudho Prakoso; Muhammad Ihsan (CV. AFDIFAL MAJU BERKAH, 2023)
The relocation of the new capital city (IKN) of the archipelago to the East Kalimantan region has a national development plan in which there are defense problems. The development of defense and security is very necessary to pay attention to strive for protective measures to anticipate external threats, one of which is reviewing from the side of Indonesia's sea defense. Indonesia's sea defense in the construction of the new capital city provides a view to improve defense strategies, especially in Indonesian sea waters. This research uses qualitative by describing with a good structure through descriptive analysis which is obtained from the study of qualified and current literature. The results of this study show that Indonesia's sea defense strategy in IKN Nusantara with efforts to implement smart defense and dual strategy is able to provide a good solution for Indonesia's sea defense.